ANALISIS STUDI DESKRIPTIF KESULITAN BELAJAR SISWA PADA MATERI PERKALIAN DAN PEMBAGIAN KELAS IV - Sabrina Putri Rahmani; Baiq Sulistia Dewi; Najwa Arni Mutari; Mar’atun Sholeha; Nia Septiani; Djuita Hidayati (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study was motivated by the importance of mastering basic multiplication facts as a foundation for mathematics learning in elementary school. The study aimed to describe the learning difficulties experienced by fourth-grade students of MI NW Badrussalam in multiplication and division of hundreds numbers. This research employed a descriptive qualitative approach. Data were collected through semi-structured interviews with the teacher and fourth-grade students, as well as documentation of students’ multiplication memorization records. Data analysis was conducted through data condensation, data display, and conclusion drawing. The results showed that the students’ main difficulty stemmed from weak mastery of basic multiplication facts. Many students had not memorized basic multiplication properly, causing difficulties in solving long multiplication and division problems involving hundreds numbers. These findings were supported by documentation data indicating that most students had not mastered the multiplication sequences from 1 to 15. Therefore, weak mastery of basic multiplication facts became the main factor affecting students’ ability to solve more complex arithmetic operations. This study is expected to serve as a reflection for teachers in designing more effective learning strategies to strengthen students’ mastery of basic multiplication facts. ABSTRACT This study was motivated by the importance of mastering basic multiplication facts as a foundation for mathematics learning in elementary school. The study aimed to describe the learning difficulties experienced by fourth-grade students of MI NW Badrussalam in multiplication and division of hundreds numbers. This research employed a descriptive qualitative approach. Data were collected through semi-structured interviews with the teacher and fourth-grade students, as well as documentation of students’ multiplication memorization records. Data analysis was conducted through data condensation, data display, and conclusion drawing. The results showed that the students’ main difficulty stemmed from weak mastery of basic multiplication facts. Many students had not memorized basic multiplication properly, causing difficulties in solving long multiplication and division problems involving hundreds numbers. These findings were supported by documentation data indicating that most students had not mastered the multiplication sequences from 1 to 15. Therefore, weak mastery of basic multiplication facts became the main factor affecting students’ ability to solve more complex arithmetic operations. This study is expected to serve as a reflection for teachers in designing more effective learning strategies to strengthen students’ mastery of basic multiplication facts.